Nursing role in early detection of cardiac amyloidosis: a case report - Eid Al shammari, Noof (International Journal of Advanced Nursing Studies, 2022)
Cardiac amyloidosis (CA) is a rare health condition that occurs due to amyloid deposits in the heart's tissues, it causes restrictive cardiomy-opathy, which leads to heart failure and death. This report discusses a case of 72-year-old Saudi male known case of hypertension, diabetes mullets, left ventricular dysfunction, and chronic kidney dysfunction presented to hospital with shortness of breath, paroxysmal nocturnal dyspnea, and orthopnea. Patient's physical examination revealed jugular vein distention, generalized pitting edema and abdominal distension. Echo image exhibited abnormal myocardial texture with moderate global hypokinesia, left ventricular D shape, and thickened interatrial sep-tum. CA diagnosis is complex, and its diagnostic accuracy is relatively limited. Delay in CA diagnosis continues to challenge clinicians, which has adverse effects on patient's quality of life, and mortality rate. Underdiagnosis mainly because disease has nonspecific symptoms which often associated with poor prognosis. To aid in early diagnosis and treatment, nurses should be aware about symptoms, diagnostic approach, and disease progression of CA.